‘Living’ database of food related policies in Honduras - International Center for Tropical Agriculture (2022)
ShiFT research involves identifying and gathering all policy documents that have a potential effect on the different components of Honduras food environment. Policies were identified in priority at the national level, but any specific sub-national policies that are relevant for our SHiFT target sites will be also included. Food environment-related policies, covering the following main sectors, were identified: (1) Agriculture & Food Production; (2) Food security & Nutrition; (3) Value chains, Trade & Markets; (4) Land Use & Urban Planning; (5) Climate Change, Environment & Natural Resources.